Measuring equity share related risk perception of investors in economically backward regions - Ranjit Singh; Jayashree Bhattacharjee (Risks, 2019)
Risk perception is an idiosyncratic process of interpretation. It is a highly personal process of making a decision based on an individual's frame of reference that has evolved over time. The purpose of this paper is to find out the risk perception level of equity investors and to identify the factors influencing their risk perception. The study was conducted using a stratified random sampling design of 358 investors. It was found that the overall risk perception level of equity investors is moderate and that the main factors affecting their risk perception are information screening, investment education, fear psychosis, fundamental expertise, technical expertise, familiarity bias, information asymmetry, understanding of the market, etc. Considering the above findings, efforts should be made to bring people with a high risk perception to the low risk perception category by providing them with training to handle or manage high-risk scenarios which will help in promoting an equity-investment culture.
Keywords: 330; risk; risk perception; equity investment; risk propensity; factor analysis